Increased Circulation and Adipose Tissue Levels of DNAJC27/RBJ in Obesity and Type 2-Diabetes - Cherian, Preethi T.; Al-Khairi, Irina; Sriraman, Devarajan; Al-Enezi, Ahmad; Al-Sultan, Dalal; AlOtaibi, Mohammed; Al-Enezi, Saad; Tuomilehto, Jaakko; Al-Mulla, Fahd; Abubaker, Jehad A.; Abu-Farha, Mohamed (Frontiers in Endocrinology, 2018)
Heat shock response is an essential cellular stress response. Dysregulation of various heat shock proteins (HSPs), within the heat shock response pathway, play a vital role in this host-defense mechanism contributing to obesity-induced insulin resistance and type 2 diabetes (T2D). Previously, we have reported changes in the expression levels of several HSPs such as HSP40, HSP60, HSP70 and HSP90 in obese compared with lean individuals. DNAJC27 is a member of the HSP40 protein family that was previously identified as a body mass index (BMI) associated locus in genome-wide association (GWAS) studies. However, not much is known about the changes in DNAJC27 expression levels in obesity and T2D. In the present study, we aimed at understanding changes in DNAJC27 expression levels in plasma, peripheral blood mononuclear cells (PBMCs) and adipose tissue in association with obesity and T2D. A total of 277 individuals enrolled including 160 non-diabetic (96 non-obese and 64 obese) and 117 T2D (45 non-obese and 72 obese) individuals. Plasma level of DNAJC27 was significantly higher in obese individuals (7.03 ± 0.68 ng/mL) compared with non-obese (4.57 ± 0.45 ng/mL) (p = 0.002). Dividing the population based on diabetes status showed that there was a significant increase in the plasma level of DNAJC27 in obese (6.90 ± 1.3 ng/mL) compared with non-obese individuals (3.81 ± 0.43 ng/mL) (p = 0.019) in the non-diabetic group. Similarly, DNAJC27 expression level was also higher in PBMCs and adipose tissue of obese individuals. DNAJC27 was found to be associated with leptin and resistin, adipokines known to be dysregulated in obesity, that stimulate inflammatory processes leading to metabolic disorders. In conclusion, our data show that DNAJC27 is elevated in obese and T2D individuals and was positively associated with obesity biomarkers such as leptin and resistin suggesting that this protein may play a role in the pathophysiology of these disorders.